Profile of patients suspected and diagnosed with COVID-19 that performed computed tomography in a Radiology Service: a descriptive study (Research, Society and Development, 2022)
The aim of the study was to describe the demographic and clinical profile of suspected patients and patients with confirmed diagnostic to COVID-19 that performed computed tomography in a Radiology Service and characterize the exams performed. Descriptive and retrospective cohort study, with data search in the patient’s electronic medical record, performed in a Radiology Service in a public hospital in the south of Brazil. The data were collected to march at december 2020 and the project was approved by the Institution’s Ethics Committee by the number 2020-054. A total of 720 patients were included in the study, being that the most of patients were women with more than 60 years old. The average length of stay was 21 days. Most of the patients observed had a positive diagnosis for COVID-19 and the vast majority of them had a favorable clinical evolution and were discharged from the hospital. In relation to the computed tomography exams performed, the exams for chest investigation prevailed followed by cranial exams. We can conclude that computed tomography was widely used to follow the respiratory symptoms related to COVID-19 and its comorbidities mainly in older patients.